2020
DOI: 10.1002/cam4.3040
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predicted significance of Ubqln2 in patients with hepatocellular carcinoma

Abstract: Purpose Hepatocellular carcinoma (HCC) is a common malignant cancer and the third leading cause of death worldwide. The molecular mechanism of HCC remains unclear. Recent studies have demonstrated that the ubiquitin‐proteasome system (UPS) is associated with HCC. Ubqln2, a member of the UPS, is abnormally expressed in HCC. However, whether Ubqln2 is associated with HCC prognosis remains unknown. Patients and Methods We analyzed the associations between overall survival and various risk factors in 355 HCC tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, efforts to identify new effective prognostic biomarkers for HCC are ongoing. According to previous reports, high expression levels of collagen type XXIV alpha 1 chain ( 43 ), ubiquilin 2 ( 44 ), sushi, von Willebrand factor type A, EGF and pentraxin domain containing 1 ( 45 ), acyl-CoA synthetase long chain family member 4 ( 46 ) and YTH N6-methyladenosine RNA binding protein 1 ( 47 ) are associated with the progression of HCC. Another study has demonstrated that in addition to the American Joint Committee on Cancer staging system, a long non-coding RNA-based risk score is another important factor affecting the overall survival of patients with HCC ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, efforts to identify new effective prognostic biomarkers for HCC are ongoing. According to previous reports, high expression levels of collagen type XXIV alpha 1 chain ( 43 ), ubiquilin 2 ( 44 ), sushi, von Willebrand factor type A, EGF and pentraxin domain containing 1 ( 45 ), acyl-CoA synthetase long chain family member 4 ( 46 ) and YTH N6-methyladenosine RNA binding protein 1 ( 47 ) are associated with the progression of HCC. Another study has demonstrated that in addition to the American Joint Committee on Cancer staging system, a long non-coding RNA-based risk score is another important factor affecting the overall survival of patients with HCC ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…UBQLN2 had been identified as a risk factor for osteosarcoma [ 14 ] and a novel marker for detecting urothelial cancer cells [ 13 ]. Overexpression of UBQLN2 in hepatocellular carcinoma patients indicates a poor prognosis [ 10 ]. However, loss of UBQLN2 led to an epithelial-to-mesenchymal transition (EMT)-like change in lung adenocarcinoma cells and promoted the invasion and metastasis of lung cancer, as was also demonstrated [ 11 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that UBQLN2 is associated with a variety of neurological diseases, including polyglutamine disease, Alzheimer's disease, and amyotrophic lateral sclerosis (ALS) [8]. In addition to neurological diseases, UBQLN2 also plays an important role in malignant tumors [9][10][11][12][13][14][15]. In our previous work, we found that UBQLN2 had a potential role in the pathogenesis of ESCC [16].…”
Section: Introductionmentioning
confidence: 99%
“…UBQLN1 expression positively correlates with patient overall outcome and survival rate in invasive breast carcinoma [27], gastric adenocarcinoma [24], and lung adenocarcinoma [26]. UBQLN2 shows similar prognostic potential in hepatocellular carcinoma (HCC) [160] and osteosarcoma [161]. However, UBQLN4 expression levels are increased in certain neuroblastomas and melanoma [38] and connected to worse outcomes.…”
Section: Ubqln Expression Levels Are Linked To Diseasementioning
confidence: 99%